Exploration of Depressive Symptoms in African American Cancer Patients - Zhang, Amy Y. (J Ment Health, 2015)
BACKGROUND: Accurately assessing depression in African American cancer patients is difficult because of the similarities of physical symptoms observed in cancer and depression. AIM: To identify universal and distinctive depressive symptoms in African American cancer patients. METHODS: Seventy-four cancer patients (34 depressed and 23 nondepressed African Americans, and 17 depressed Whites) were interviewed. Qualitative and quantitative analyses were conducted. RESULTS: Compared to nondepressed African Americans, depressed African Americans reported irritability, social isolation, insomnia, fatigue, and crying (p ≤ .05) more frequently over time. Compared to depressed Whites, they reported sadness, frustration, and intrusive thoughts less frequently (p ≤ .05), but insomnia and fatigue more frequently (p ≤ .05) during cancer treatment. There was little racial difference at the time of interview. CONCLUSION: Depressed African American cancer patients may benefit from more culturally sensitive depression measures that consider symptoms of irritability, social isolation, and altered expressions of depressive mood.